2017
DOI: 10.1007/s00277-017-2958-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cachexia on outcomes in aggressive lymphomas

Abstract: Cancer cachexia is defined as a state of involuntary weight loss, attributed to altered body composition with muscle mass loss and/or loss of adiposity. Identifying the association between cancer cachexia and outcomes may pave the way for novel agents that target the cancer cachexia process. Clinical parameters for measurement of cancer cachexia are needed. We conducted a single-institution retrospective analysis that included 86 NHL patients with the aim of identifying an association between cancer cachexia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…Altogether, we identified 21 studies published between 1980 and 2017 and reporting on 31 047 cancer patients as shown in Table . These studies provided acceptably reliable data for all of the 14 cancer entities selected for analysis.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Altogether, we identified 21 studies published between 1980 and 2017 and reporting on 31 047 cancer patients as shown in Table . These studies provided acceptably reliable data for all of the 14 cancer entities selected for analysis.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Cancer cachexia is a multifactorial condition of involuntary weight loss that leads to progressive functional impairment in patients and has been associated with treatment failure and poor survival (Camus et al , ; Karmali et al , ). Recent research has identified a number of inflammatory pathways and cytokines and metabolic dysregulation that contribute to the development of cachexia (Kumar et al , ; Kemik et al , ; Martin et al , ).…”
mentioning
confidence: 99%
“…Alternatively, we hypothesised that lymphoma cells can mobilise FAs from adipose tissues, leading to an elevation in plasma FA levels concomitantly with body fat loss. This metabolic syndrome, called cancer cachexia-associated adipopenia, is observed in DLBCL patients, and is associated with poorer prognostic outcomes than that of non-adipopenic patients (Camus et al, 2014;Huang et al, 2013;Karmali et al, 2017). Hence, our results combined with others indicate that lymphoma causes a systemic increase in FA levels via increased FA synthesis and/or mobilisation from adipose tissues.…”
Section: Discussionsupporting
confidence: 69%
“…Lymphoma cells and the splenic lymphoma environment upregulated FA synthesis, forming an environment that actively synthesize lipid. As discussed, lymphoma growth was also associated with development of cachexia-associated fat loss, which has been observed to increase or to be associated with systemic FA levels Karmali et al, 2017). We speculate that the lipid excess-NK suppression axis may also extend to other forms of tumours, as increased lipid metabolism and development of cancer-cachexia are commonly observed in cancers (Baron et al, 2004;Liu et al, 2017;Porporato, 2016).…”
Section: The Nutrient and Metabolite Levels In B Cell Lymphoma Enviromentioning
confidence: 59%
See 1 more Smart Citation